Enhancement of heat transfer for ground source heat pump systems - Mori, Hiromi (2010)
Uptake of geothermal heat pump (GSHP) systems has been slow in some parts of the world due to the unpredictable operational performance, large installation space requirement and high installation costs. Therefore, design modification was searched in order to improve the feasibility. With regard to relatively small impact of the construction costs, efficient thermal energy collection was targeted in horizontal ground-loop systems with shallow underground construction.